2022
DOI: 10.3389/fonc.2022.888755
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Liver-Directed Radiotherapy in Combination With Lenvatinib for Hepatocelluar Carcinoma With Macroscopic Tumor Thrombosis

Abstract: BackgroundThis study aimed to compare the clinical outcomes of patients with hepatocellular carcinoma (HCC) and macroscopic tumor thrombosis who were treated with lenvatinib with or without combined liver-directed radiotherapy (LRT).MethodsFrom the institutional registry, we enrolled 82 patients diagnosed with HCC involving macroscopic tumor thrombosis and treated with lenvatinib monotherapy (non-LRT group, n = 54, 65.9%) or lenvatinib in combination with LRT (LRT group, n = 28, 34.1%). Patients were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To date, there are fewer studies on lenvatinib for the treatment of HCC with PVTT. In a study by Yu et al [32], lenvatinib treatment of HCC patients with macroscopic tumor thrombosis had a 1-year OS rate of 37.7%. In our study, the 1-year OS rate for lenvatinib treatment of HCC with PVTT was 39.5%, similar to the result of the study by Yu.…”
Section: Discussionmentioning
confidence: 98%
“…To date, there are fewer studies on lenvatinib for the treatment of HCC with PVTT. In a study by Yu et al [32], lenvatinib treatment of HCC patients with macroscopic tumor thrombosis had a 1-year OS rate of 37.7%. In our study, the 1-year OS rate for lenvatinib treatment of HCC with PVTT was 39.5%, similar to the result of the study by Yu.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, this is the first clinical study comparing SBRT in combination with lenvatinib and lenvatinib alone for the treatment of HCC with PVTT. Recently, Yu et al [ 38 ] conducted a retrospective clinical study of liver-directed radiotherapy (LRT) in combination with lenvatinib versus lenvatinib alone for the treatment of HCC with macroscopic tumor thrombosis and extrahepatic metastases. Their study showed that during a median follow-up period of 5.4 months (1.4–17.5 months), the combination treatment group had significantly better PFS (67.2% vs. 35.0% at 6 months, p = 0.008) and IHPFS (74.3% vs. 43.3% at 6 months, p = 0.008) were significantly better than in the monotherapy group, but there was no statistically significant difference in overall response rate (32.1% vs. 20.4%, p = 0.15) and OS rate (64.1% vs. 37.7% at 12 months, p = 0.06).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst clinical study comparing SBRT in combination with lenvatinib and lenvatinib alone for the treatment of HCC with PVTT. Recently, Yu et al [37] conducted a retrospective clinical study of liver-directed radiotherapy (LRT) in combination with lenvatinib versus lenvatinib alone for the treatment of HCC with macroscopic tumor thrombosis and extrahepatic metastases. Their study showed that during a median follow-up period of 5.4 months (1.4 to 17.5 months), the combination treatment group had signi cantly better PFS (67.2% vs. 35.0% at 6 months, p = 0.008) and IHPFS (74.3% vs. 43.3% at 6 months, p = 0.008) were signi cantly better than in the monotherapy group, but there was no statistically signi cant difference in overall response rate (32.1% vs. 20.4%, p = 0.15) and OS rate (64.1% vs. 37.7% at 12 months, p = 0.06).…”
Section: Discussionmentioning
confidence: 99%